2002
DOI: 10.1006/viro.2001.1246
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Antigenicity of the Hepatitis B Virus HBsAg Protein Arising as a Consequence of Sequence Changes in the Overlapping Polymerase Gene That Are Selected by Lamivudine Therapy

Abstract: The prevalence of hepatitis B virus vaccine escape mutants has increased as a consequence of the introduction of global vaccination programs. Furthermore and as a consequence of the organization of the genome of hepatitis B virus (HBV) into overlapping reading frames, the selection of polymerase mutants during long-term lamivudine therapy can select viruses with changes in the overlapping S gene coding for the hepatitis B small antigen (HBsAg). We have investigated the role of lamivudine in selecting HBV mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
180
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(190 citation statements)
references
References 32 publications
9
180
0
1
Order By: Relevance
“…The triple mutation V519L/L526M/ M550V causes the concomitant amino acid substitutions E164D and I195M in the S protein. It has been shown recently that this triple mutant has a reduced affinity to anti-HBs antibodies, similarly to what happens with the well-known hepatitis B vaccine escape mutant G145R (Torresi et al 2002, Cooley et al 2003.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The triple mutation V519L/L526M/ M550V causes the concomitant amino acid substitutions E164D and I195M in the S protein. It has been shown recently that this triple mutant has a reduced affinity to anti-HBs antibodies, similarly to what happens with the well-known hepatitis B vaccine escape mutant G145R (Torresi et al 2002, Cooley et al 2003.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, one sample displayed a third, previously described (Torresi et al 2002, Cooley et al 2003 lamivudine resistance mutation, namely V519L. The triple mutation V519L/L526M/ M550V causes the concomitant amino acid substitutions E164D and I195M in the S protein.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This process results in new, closely-related viral species; as a result, at any given time in a particular host the viral population consists of a swarm of similar but discrete viruses. 6,7 Vaccine escape mutants up to 95% of recipients. 8 The envelope gene of HBV produces proteins of three different lengths: two larger proteins, preS1 and preS2, as well as the smaller S protein.…”
Section: Features Of the Virusmentioning
confidence: 99%
“…The triple lamivudine resistance mutation causes the concomitant amino acid substitutions E164D and I195M in the HBsAg as a result of the overlapping reading frames of the envelope and polymerase genes (Locarnini, 1998). It has been shown that both E164D and I195M substitutions reduce in vitro affinity of HBsAg to anti-HBs antibodies, similar to the HBV vaccine escape mutant G145R (Torresi et al, 2002). The HBsAg Y100C substitution is also frequently found among occult HBV infection carriers.…”
Section: Hbv Variants In the General Population Vs Among Hemodialysimentioning
confidence: 99%